EJBM 2021
DOI: 10.7176/ejbm/13-6-01
|View full text |Cite
|
Sign up to set email alerts
|

An AHP Framework to Evaluate Barriers and Potential Tensions to Green Supply Chain Management in the Food and Beverage Industry

Abstract: With an increasing awareness of climate change and the need for sustainable processes, a growing number of studies have addressed green supply chain management (GSCM), its drivers, barriers, and implementation frameworks. However, despite the importance of environmental practices, industries are reluctant to implement GSCM activities, as many obstacles can arise while initiating GSCM in traditional supply chain management (TSCM). The previous literature review indicated substantial research on the barriers tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 81 publications
(211 reference statements)
0
0
0
Order By: Relevance
“…Supply chain management comprises a collection of interconnected activities aimed at achieving seamless coordination and communication within these operations, ultimately striving to enhance overall efficiency throughout the process [4,23]. Effective Inventory Management DOI: http://dx.doi.org/10.5772/intechopen.113282 supply chain strategy hinges on the sharing of product and production information among its members.…”
Section: Vendor-managed Inventorymentioning
confidence: 99%
“…Supply chain management comprises a collection of interconnected activities aimed at achieving seamless coordination and communication within these operations, ultimately striving to enhance overall efficiency throughout the process [4,23]. Effective Inventory Management DOI: http://dx.doi.org/10.5772/intechopen.113282 supply chain strategy hinges on the sharing of product and production information among its members.…”
Section: Vendor-managed Inventorymentioning
confidence: 99%
“…At the same time, there are few resources to implement cleaner methods of production in most LMICs (Abdellatif &Graham, 2019). Additionally, reviewed literature has shown that the green concept is under researched in the manufacturing sectors of developing countries (Abdellatif & Graham, 2019;Tumpa et al, 2019;Uddin et al, 2019 andAhmed, 2021), majority of which are in Africa (Ahmed, 2021). This is the case in spite of the fact that environmental protection is important for the development of a nation's economy.…”
mentioning
confidence: 99%